Penerapan Electronic Costumer Relationship Management Penjualan Berbasis Web - Heri Purwanto; Ditta Yuniana; Mohammad Erdda Habiby; Hari Hermawan (INTERNAL (Information System Journal), 2021)
Kedai Mandiri is a restaurant on Jalan Gatot Subroto No.40 Malabar Bandung, West Java which serves food and beverage culinary sales, Kedai Mandiri still uses the medium of delivering information on simple food and beverage menu data and services where the system runs on restaurants that are still semi-computerized. So that the sales of food and beverage products and services are still not optimal. In terms of the problems faced, then how do you apply Electronic Customer Relationship Management to Kedai Mandiri sales that can explain the fabric in detail so that the product menu and services received can be immediately responded to by customers so that they can access the required information data anytime and anywhere, related one to respond to this by creating a website-based sales E-CRM application at Kedai Mandiri using a prototype method approach that develops it by demonstrating the concept, design experiments and look for various problems and solutions to resolve misunderstandings between customers and developers in stages. This application can be expected to help the problems experienced by the Kedai Mandiri restaurant, and the system can be further developed using a mobile application.